Nutrients and bioactive compounds content of Baillonella toxisperma, Trichoscypha abut and Pentaclethra macrophylla from Cameroon - Fungo, R.; Muyonga, John H.; Kaaya, A.; Okia, C.; Tieguhong, J.C.; Baidu-Forson, Joseph Jojo (Wiley, 2015)
Baillonella toxisperma, Pentaclethra macrophylla and Trichoscypha abut are important foods for communities living around forests in Cameroon. Information on the nutritional value and bioactive content of these foods is required to establish their contribution to the nutrition and health of the communities. Samples of the three foods were obtained from four villages in east and three villages in south Cameroon. The foods were analyzed for proximate composition, minerals and bioactive content using standard chemical analysis methods. T. abut was found to be an excellent source of bioactive compounds; flavonoids (306 mg/100 g), polyphenols (947 mg/100 g), proanthocyanins (61.2 mg/100 g), vitamin C (80.05 mg/100 g), and total oxalates (0.6 mg/100 g). P. macrophylla was found to be a rich source of total fat (38.71%), protein (15.82%) and total fiber (17.10%) and some bioactive compounds; vitamin E (19.4 mg/100 g) and proanthocyanins (65.0 mg/100 g). B. toxisperma, was found to have high content of carbohydrates (89.6%), potassium (27.5 mg/100 g) and calcium (37.5 mg/100 g). Flavonoids, polyphenols, vitamins C and E are the main bioactive compounds in these forest foods. The daily consumption of some of these fruits may coffer protection against some ailments and oxidative stress. Approximately 200 g of either B. toxisperma or P. macrophylla, can supply 100% iron and zinc RDAs for children aged 1–3 years, while 300 g of the two forest foods can supply about 85% iron and zinc RDAs for non-pregnant non-lactating women. The three foods provide 100% daily vitamins C and E requirements for both adults and children. The results of this study show that Baillonella toxisperma, Pentaclethra macrophylla and Trichoscypha abut can considerably contribute towards the human nutrient requirements. These forest foods also contain substantial levels of health promoting phytochemicals notably flavonoids, polyphenols, vitamins C and E. These foods therefore have potential to promote nutrition and health, especially among forest dependent communities who consume them in substantial amounts.